Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "equals", "squared". There are no equations in the question - only a lot of disjoint expressions.
To simplify the expression 12p + 19q + p - 5q - 3p, we first combine like terms. Combining the p terms, we have 12p + p - 3p, which simplifies to 10p. Combining the q terms, we have 19q - 5q, which simplifies to 14q. Therefore, the simplified expression is 10p + 14q.
p+2 = 2-3p p+3p = 2-2 4p = 0 p = 0
4p+2 = 3p-7 4p-3p = -7-2 p = -9
3p2-2p-5 = (3p-5)(p+1) when factored
answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}
To simplify the expression 12p + 19q + p - 5q - 3p, we first combine like terms. Combining the p terms, we have 12p + p - 3p, which simplifies to 10p. Combining the q terms, we have 19q - 5q, which simplifies to 14q. Therefore, the simplified expression is 10p + 14q.
4p - 12 = 3p - 8 - 9p 4p - 3p + 9p = -8 + 12 10p = 4 p = 0.4 (or 2/5)
the product of 10p (p–q) is 10p²-10pq Given: 10p (p–q) To find : the product of 10p (p–q) Solution: we have to find the product of 10p (p–q). so product of any number means the multiplication multiply (p–q). by 10p we get, =10p× (p–q) =10p×p-10p× q =10p²-10pq the product of 10p (p–q) is 10p²-10pq
3p
10p + 5p - p = 15p - p = 14p
p+2 = 2-3p p+3p = 2-2 4p = 0 p = 0
3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7
-5 + 3p - p = -5 + 2p
p2 + 3p = p (p + 3)
10p = 180 p = 18
3(p+7) - (4p-1) = -5(2p-3) + 1 Multiplying out the brackets: 3p + 21 - 4p + 1 = -10p + 15 + 1 Simplifying: 22 - p = 16 - 10p 9p = -6 p = -2/3 To check, you could substitute p = -2/3 into the original equation and check that it holds.
100 - 3p = 88 -3p = 88 - 100 -3p = -12 p= (-12/-3) p = 4 so 100 - 3 * 4 = 88